Field reports, Babs and Loren Padelford, fall 1989 - Padelford, Babset al; Padelford, Lorenet al (1989)
Field reports submitted by Babs and Loren Padelford with several contributors for fall 1989. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1989. Epson - sheet feed